INDUKSI PERKECAMBAHAN BIJI SIRSAK ( Annona muricata ) MENGGUNAKAN AIR KELAPA MUDA - Andriani, Andriani; Advinda, Linda; Novi, Novi (STKIP PGRI Sumbar, 2013)
ABSTRACTAnnona muricata L. is a kind of plant growing and fruiting perennially if the water demond is apparently sufficed. A. muricata L. seed has averagely less germination power, however it can be improved by the induction. Coconut water is proved to induct that power because it contains some essences supporting seed growth: auxin, gibberellind and cytokinins. This research was carried out at 13rd January until25th February in Physiology Laboratory of Biology Departement Unversity of Padang.This is a descriptive research which used six concentrates of coconut water are: 0%,20%, 40%, 60%, 80% and 100% with every concentrate is put on four plastic scuttles. The observation was held six week to find out days when seed started growing and amount of seed germinating. The result showed that germination in 60% appeared in19th day. The writer summarizes that coconut water dad not be able to inductgermination of A. muricata seed. The result evidenced that from 120 seeds germination, there werw only 7 seeds started growing.